PERANAN STRATEGIS HUMAS DALAM MEMPERTAHANKAN IMAGE DAN REPUTASI SD PLUS NURUL HIKMAH PAMEKASAN - Ismi Noerul Izzah; Atiqullah Atiqullah (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The existence of the community is one of the keys to the success and progress of the quality of educational institutions because when educational institutions are able to provide trust in the community they always support the activities of the institution. in accordance with the opinion of Mujammil Qamar in his book, that one of the keys to the progress of educational institutions is public trust, when they have trust in educational institutions, they will fully support, not only by sending their children to the education institution, but also recommending others to do so the same as him. Conversely, when the community does not believe, they do not not include their education institution's sons and daughters, but even influence their neighbors or employees, this means that the community is a strategic component that must be given full attention by education managers.